Program Belajar Intensif Berbasis Tutorial Digital Sebagai Solusi Melemahnya Sektor Usaha Berbasis Pendidikan Non-Formal Di Masa Pandemi Covid-19 di Banten - Silalahi, Ronald Maraden Parlindungan; Santasa, Modena (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2023)
The role of foreign languages ​​(especially English) which is very fundamental in the era of globalization has implications for the high interest in learning English in both formal and informal contexts. However, teaching English in a formal context is often not able to answer the expectations of language learners for quality. Therefore, non-formal learning through foreign language institutions is an option. On the one hand, this need has an impact on the proliferation of language institutions in the last few decades. The Covid-19 pandemic in the last two years has had an impact on the weakening of this non-formal sector. Community service activities in the Serang and Serpong areas are directed to provide answers to the complexity of this problem. Through an enrichment program carried out in 4 stages (initiation, planning, execution and implementation), a solution was found that the development of a private tutor program could be one solution to the weakening of the non-formal education sector during the pandemic. Through an enrichment program focusing on three themes (needs analysis, selection of teaching materials, and making syllabus), language institutions at the two implementation locations are directed to be able to form private programs within the framework of appropriate and efficient management. Most of the agencies that run feel the most impact when the program is implemented. However, other enrichment activities are still needed to be able to monitor and improve the quality of language institutions and have economic value.